TEGANGAN GESER ULTIMIT PEREKAT EPOXY – RESIN TEGAK LURUS SERAT PADA SAMBUNGAN KAYU - Putra, Dharma (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008, 2012)
This research aims to determine ultimate shear stress at timber connection with 18% water content subjected to compressive load perpendicular to fibre orientation. Sample tests of connection were made from camfer timber of 6/15 connected at it both sides to other timber of 2 x 4/15. Sample tests were treated in 5 variation with fastening interfase 15 cm wide and various length of 10 cm, 15 cm, 20 cm, 25 cm, and 28 cm there were 3 repitition in each treatment. Sample tests were subjected to axial compressive increasing load with increase step of 2,5 kN until failure. Result of research shown that the value of shear stress of epoxy-resin glue due to compressive load are as follows. The average ultimate shear strength of connection with treatment I, II, III, IV and V are 14,208 kg/cm2, 16,042 kg/cm2, 17, 042 kg/cm2, 18,467 kg/cm2 and 20,268 kg/cm2 respectively. The minimum ultimate shear strength 14,21 kg/cm2, the maximum ultimate shear strength is 20, 27 kg/cm2 and the average ultimate shear strength is 17,19 kg/cm2. It can be conclude that shear strength is relatively high and could be use as alternative connection device. Connection using epoxy-resin has high efficiency but it is relatively brittle
Keywords: tegangan geser ultimit, epoxy-resin, kadar lengas, kayu kamfer